2022
DOI: 10.3390/app12115589
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Implantitis: A New Definition Proposal Based on Unnatural Spatial Arrangement and Late Mechanical Coupling between Two Cortical Bone Layers during Osseointegration Phase Part II

Abstract: To date, the term peri-implantitis has been mostly associated with bacterial or foreign body reaction as primary factors of its development. Because of this, researchers’ and clinicians’ attention regarding treatment possibilities were directed into the solutions on the basis of surface modifications, debridement, and antibiotics. After years of clinical observations and poor results in treatment of peri-implantitis, a new proposal of this condition is presented, shifting our way of thinking regarding bone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Stefan et al inferred that the marginal bone loss was a result of natural changes in the bone's morphology in response to the implant, such as a decrease in the convexity of the outer surface and concavity of the inner bone [53]. They found that when implants showed a vertical bone loss, apical bone part rather increased.…”
Section: Marginal Bone Lossmentioning
confidence: 99%
“…Stefan et al inferred that the marginal bone loss was a result of natural changes in the bone's morphology in response to the implant, such as a decrease in the convexity of the outer surface and concavity of the inner bone [53]. They found that when implants showed a vertical bone loss, apical bone part rather increased.…”
Section: Marginal Bone Lossmentioning
confidence: 99%
“…Peri‐implantitis and periodontitis refer to the progressive inflammation of the supporting structure of implants and teeth. An imbalance between the internal immunological response of the host and the foreign body response causes these conditions, 16 which in turn leads to implant surface contamination, alveolar bone loss, tooth/implant loss, and tooth mobility 17 . The distinctive clinical profile in patients with periodontal inflammation and SSc includes widened periodontal ligament, 18 decreased bleeding index and probing depth, and increased periodontal attachment loss 2 .…”
Section: Introductionmentioning
confidence: 99%